Gold‐Catalyzed C−H Functionalization Polycondensation for the Synthesis of Aromatic Polymers. Issue 49 (3rd November 2020) - King, Eric R.; Tropp, Joshua; Eedugurala, Naresh; Gonce, Lauren E.; Stanciu, Sonia; Azoulay, Jason D.
Abstract: Homogeneous gold (Au) complexes have demonstrated tremendous utility in modern organic chemistry; however, their application for the synthesis of polymers remains rare. Herein, we demonstrate the first catalytic application of Au complexes toward the polycondensation of alkyne‐containing comonomers and heteroarene nucleophiles. Polymerization occurs through successive intermolecular hydroarylation reactions to produce high molecular weight aromatic copolymers with 1, 1‐disubstituted alkene backbone linkages. Clear correlations between the rate and degree of polymerization (DP) were established based on catalyst structure and counterion pairing, thus enabling polymerization reactions that proceeded with remarkable efficiency, high reactivity, and exceptional DPs. The reactivity is broad in scope, enabling the copolymerization of highly functionalized aromatic and aliphatic monomers. These results highlight the untapped utility of Au catalysis in providing access to new macromolecular constructs. Abstract : Homogeneous gold catalysis enabled the C−H functionalization polycondensation of alkyne‐containing comonomers and heteroarene nucleophiles (see scheme). The polymerization is broad in scope and proceeded with remarkable efficiency to produce high molecular weight aromatic copolymers. These results highlight the untapped utility of gold in the construction of new macromolecular systems.